The impact of renewable energy auctions on global grid greening: A comparative analysis across economies - Dizhou Huang (Energy Strategy Reviews)
Renewable energy (RE) auctions have emerged as an essential strategy for countries who want to diversify their energy mix due to the climate change challenges. While earlier research predominantly establishes the fact that bidding positively influences RE capacity, they mostly fail to capture the mixed success that depends on the economic and corporate environment. This study aims to complement it by assessing the effects of RE auctions on the uptake of renewable energy in countries characterized by fluctuations in economic conditions or different business climates. This paper analyzes the factors in bid efficacy with a dataset of 98 countries from 2000 to 2020 through cluster analysis of the corporate climate quality index and DID analysis of sequential policy endogenously. The paper also shows that RE auctions are, on average, a successful policy instrument in growing the share of renewable energy capacity. However, their effectiveness strongly correlates with the context of the country. For countries with stable corporate environments, the average treatment effect is stronger, while for those experiencing financial or structural unpredictability, the issue of RE auctions should be better twiddled. These close results emphasize the need for the elaboration of specific policies concerning auctions that would take into consideration the features of a particular country's economy and legislation. Therefore, to sum it up, RE auctions are a possible instrument for augmenting the worldwide RE generation capacity. However, their potential is not enormous, and the effects are not equitable among all countries. The government should use outcome data to understand the conditions necessary for the long-term success of RE auctions.